2022
DOI: 10.4193/rhinol/21.055
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlation and assessment of olfactory dysfunction with n-butanol in COVID-19 patients: our experience

Abstract: Background: Studies showed olfactory disturbances in COVID patients. This has attracted focus of clinicians as an easy clinical screening tool in suspected population. Material and methods: 70 mild and moderate category COVID-19 RT-PCR positive patients, more than 10 years of age were tested on day of admission for olfaction with serial dilution of n-butanol and asked to grade severity of their olfactory dysfunction according to visual analogue score from 1-10. Results: Fatigue 42 (93.33%), sore throat 37 (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The COVID-19 positive individuals answered to the queries and it was identified that most of them had the clinical manifestations of fever (74.13%), sore throat/dry cough (65.51%), nasal stuffiness or rhinorrhoea (60.34%) and myalgia/fatigue (53.44%) and GI symptoms (34.38%). The various systematic reviews and meta-analysis and other studies have also reported the common occurrence of fever, cough, fatigue & rhinorrhoea/ nasal stuffiness as the common symptoms in COVID-19 infected patients [17][18][19][20]. On the other hand, all the COVID-19 negative individuals also had a history of fever and a considerable group had dry cough/sore throat and few had a history of myalgia only.…”
Section: Discussionmentioning
confidence: 98%
“…The COVID-19 positive individuals answered to the queries and it was identified that most of them had the clinical manifestations of fever (74.13%), sore throat/dry cough (65.51%), nasal stuffiness or rhinorrhoea (60.34%) and myalgia/fatigue (53.44%) and GI symptoms (34.38%). The various systematic reviews and meta-analysis and other studies have also reported the common occurrence of fever, cough, fatigue & rhinorrhoea/ nasal stuffiness as the common symptoms in COVID-19 infected patients [17][18][19][20]. On the other hand, all the COVID-19 negative individuals also had a history of fever and a considerable group had dry cough/sore throat and few had a history of myalgia only.…”
Section: Discussionmentioning
confidence: 98%
“…The COVID-19 positive individuals answered to the queries and it was identified that most of them had the clinical manifestations of fever (74.13%), sore throat/dry cough (65.51%), nasal stuffiness or rhinorrhoea (60.34%) and myalgia/fatigue (53.44%) and GI symptoms (34.38%). The various systematic reviews and meta-analysis and other studies have also reported the common occurrence of fever, cough, fatigue & rhinorrhoea/ nasal stuffiness as the common symptoms in COVID-19 infected patients [17][18][19][20]. On the other hand, all the COVID-19 negative individuals also had a history of fever and a considerable group had dry cough/sore throat and few had a history of myalgia only.…”
Section: Discussionmentioning
confidence: 98%
“…The various systematic reviews and meta-analysis and other studies have also reported the common occurrence of fever, cough, fatigue & rhinorrhoea/nasal stuffiness as the common symptoms in COVID-19 infected patients. [ 17 – 20 ]. On the other hand, all the COVID-19 negative individuals also had a history of fever and a considerable group had dry cough/sore throat and few had a history of myalgia only.…”
Section: Discussionmentioning
confidence: 99%